Mechanical Properties Restoration of API 5L X60 Carbon Steel through Hot Induction Bending Followed by Quenching and Tempering Treatment - Kirana, Dois Dita Wahyu; Hasibuan, Fardin; Hakim, Arif Rahman; Adlinizar, Muhammad Fahrell (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2025)
Pipe bending is a critical process in the oil and gas industry to accommodate complex terrain while maintaining pipeline integrity. This study investigates the mechanical and micro structural responses of API 5L X60 seamless carbon steel pipes subjected to hot induction bending followed by quenching and tempering. Tensile testing, hardness measurements, and optical microscopy were employed to characterize the changes induced by these treatments. Post-treatment results demonstrated an increase in ultimate tensile strength from 580 N/mm² to 606 N/mm² (4.4%) and yield strength from 455 N/mm² to 495 N/mm² (8.7%), accompanied by a reduction in elongation from 27% to 23% and a slight decrease in hardness from 206 HV to 199 HV. Micro structural observations revealed finer grains (ASTM grain size 9.5) and the presence of tempered martensite, contributing to improved strength and toughness. The enhancements are attributed to strain hardening, phase transformation, and stress relief during tempering. These findings suggest that integrating hot bending with appropriate heat treatment effectively optimizes pipe performance for demanding service conditions.